Pemikiran Rakawi Yusuf dengan Rujukan Khusus Kepada Novel Melati Sarawak 1932 - Nordi Achie (1999)
Based on the novel Melati Sarawak, this article aims to trace the thoughts of Muhammad Rakawi Yusuf, the author, and his contribution to the development of the Malay community.